Journals and CPD. (2nd April 2016) - Bryson, David
Abstract: One of the significant tools for supporting continuing professional development (CPD) is the Institute of Medical Illustrators (IMI) owned publication the Journal of Visual Communication in Medicine. Other journals, for example the Journal of Biological Photography, The British Journal of Photography, British Medical Journal and specialist journals associated with specific areas of medicine, education and illustration, are also helpful. The aim of this paper is to look at journals and CPD together with activities to help you engage with current literature, practice and research. If you look at the examples of CPD activities suggested by both IMI and the Health Professions Council (HPC) one of the recurring themes is the role of journals (Table 1 ). Journals, alongside conferences, regional and national meetings, are key means of dissemination of research and support for professional development.